Essays on finance and macroeconomy - Simonsen, Axel André (2009)
I study the asset-pricing implications in an cnviromncnt with feedback traders and rational arbitrageurs. Feedback traders are defined as possible naive investors who buy after a raise in prices and sell after a drop in prices. I consider two types of feedback strategies: (1) short-term (SF), motivated by institutional rulcs as top-losscs and margin calls and (2) long-tcrm (LF), motivated by representativeness bias from non-sophisticated investors. Their presence in the market follows a stochastic regime swift process. Short lived assumption for the arbitrageurs prevents the correction of the misspricing generated by feedback strategies. The estimated modcl using US data suggests that the regime switching is able to capture the time varying autocorrclation of returns. The segregation of feedback types helps to identify the long term component that otherwise would not show up due to the large movements implied by the SF typc. The paper also has normativo implications for practioners since it providos a methodology to identify mispricings driven by feedback traders.